Lactobacillus reuteri-derived HDCA suppresses PEDV replication while alleviating virus-triggered inflammation in piglets - Bian, Zhibiao; Li, Qianqian; Gou, Hongchao; Li, Yan; Jiang, Zhiyong; Chu, Pinpin; Zhai, Shaolun; Kang, Huahua; Li, Chunling; Zhao, Guanghui (Frontiers in Microbiology, 2025)
BackgroundPorcine epidemic diarrhea virus (PEDV) causes severe diarrhea, vomiting, and high mortality in neonatal piglets, but no fully effective treatments or vaccines are currently available. Although gut microbiota transplantation can alleviate post infection symptoms, the specific protective bacterial strains or metabolites involved, along with their underlying mechanisms of action against PEDV, remain unclear.ResultsOral administration of L. reuteri GZ-1 or its metabolite hyodeoxycholic acid (HDCA) to three-day-old piglets significantly mitigated clinical symptoms and improved survival outcomes following PEDV challenge. This protection was achieved through five-day pretreatment preceding viral exposure. Both interventions substantially preserved the intestinal architecture, maintaining normal villus height and goblet cell density while markedly reducing PEDV loads in jejunal tissue. Metabolomic profiling established HDCA—a secondary bile acid derivative of L. reuteri metabolism—as the core protective mediator. The direct antiviral activity of HDCA against PEDV was subsequently confirmed through complementary in vitro and in vivo experimental validation. Integrated transcriptomic and proteomic analyses revealed a dual mechanistic pathway underlying HDCA efficacy: (1) suppression of NF-κB-driven inflammatory cascades and (2) activation of interferon-stimulated gene 15 (ISG15)-dependent antiviral pathways.ConclusionThis study establishes the L. reuteri-HDCA-TGR5-IFNβ-ISG15 metabolic axis as a novel antiviral pathway. This study identified microbial-derived HDCA as a key effector metabolite that mediates protection against PEDV through the coordinated suppression of inflammation and enhancement of antiviral defenses. These findings highlight microbial-metabolic crosstalk as a promising therapeutic strategy against enteric coronaviruses and provide foundational evidence for commensal-derived interventions to manage porcine epidemic diarrhea.